C3N4/PDA S‐Scheme Heterojunction with Enhanced Photocatalytic H2O2 Production Performance and Its Mechanism. (9th May 2022) - Zhang, Xidong; Yu, Jiaguo; Macyk, Wojciech; Wageh, S.; Al‐Ghamdi, Ahmed A.; Wang, Linxi
Abstract: Developing a high‐performance photocatalyst is important for realizing efficient photocatalytic H2 O2 generation. Herein, a novel step‐scheme (S‐scheme) heterojunction photocatalyst C3 N4 /PDA (CNP) comprised of ultrathin g‐C3 N4 (U‐CN) and polydopamine (PDA) is constructed by in situ self‐polymerization. The optimal photocatalyst presents an excellent H2 O2 production rate of 3801.25 µmol g −1 h −1 under light irradiation, which is about 2 and 11 times higher than that of pure U‐CN and PDA, respectively, and exceeds most of the reported C3 N4 ‐based photocatalysts. The improvement of photocatalytic activity is ascribed to the synergistic effect of improved light absorption and promoted charge separation and transfer induced by the S‐scheme heterojunction. In situ irradiated X‐ray photoelectron spectroscopy (ISI‐XPS) reveals that the charge transfer route matches the S‐scheme mechanism. Rotating disk electrode (RDE) measurements and electron spin resonance (ESR) spectroscopy verify that H2 O2 is produced by a two‐step one‐electron process. This work highlights a promising method to construct high‐performance S‐scheme heterojunction photocatalysts through the hybridization of PDA and C3 N4 . Abstract : Benefiting from the construction of C3 N4 and a polydopamine (PDA) S‐scheme heterojunction, the H2 O2 yield over a C3 N4 /PDA hybrid photocatalyst is significantly enhanced. The S‐scheme heterojunction can efficiently improve the electron transfer, and the electron with powerful reduction ability is preserved to participate in O2 reduction for H2 O2 production. It is a promising strategy for efficient H2 O2 production.